ANALISIS TINGKAT BAHAYA BANJIR BANDANG DENGAN METODE FFPI DI SUB DAS AIR BETUNG - Azizah, Barrorotul (Universitas PGRI Semarang, 2024)
Pagar Alam City is one of the areas in Indonesia which is a disaster-prone area, one of which is flash floods. Pagar Alam City is very at risk of flash floods based on DIBI from BNPB in the period 2012 to 2022, in the last 10 years there have been 5 flash floods with damage to 1 unit of house severely damaged and some debris washed away in parts of the building, damage to irrigation canals ± 50 m long and 2 m high, damage to retaining walls 25 m long and 40 m high and ± 30 ha of cropland damaged and ± 73 hectares of agricultural land affected by the disaster. This research was conducted to determine the level of vulnerability to flash floods in the Air Betung sub-watershed. Hazard level mapping is a step taken to determine the level of vulnerability by analyzing slope maps, land use maps, soil texture maps and canopy cover maps. The vulnerability index was analyzed using the FFPI method processed in the Arcgis 10.4 program. The results of the vulnerability index are classified into three classes, namely low class, medium class and high class. Pagar Alam Selatan sub-district is a sub-district that has a high index value, while Pajar Bulan sub-district has the lowest index of flash flood vulnerability in the Air Betung sub-watershed.